Developing of Small and Medium Enterprises for Poverty Alleviation in Indonesia: Lesson Learned from OTOP Program in Thailand - Pasaribu, Sahat M. (Analisis Kebijakan Pertanian, 2016)
The Government of Thailand has launched programs to help alleviate the people from poverty. Thailand is considered as a consistent country in terms of rural development amid some experiences in political discourages. Despite the negative impact of economic crisis, Thailand had shown their capability to recover from such a difficult situation. With the participation of the people, this country is currently taking their opportunities to improve domestic economy through small and medium enterprises development. OTOP (One Tambon One Product) Program is one out of many policies to support groups of people to develop local wisdom in cooperation with private sectors under the guidance of local administration to produce and to enhance local-specific high value commodities. Indigenous knowledge and inherited wisdom are explored to its fullest for modern and commercial products. Three-way coordination policy practiced in rural development management has been improved to certain level shown by the increasing production of varied high grade commodities entering both domestic and international market. Government efforts to produce reliable database is the key point to initiate and encourage investment in rural areas. This paper describes the experience of Thailand in rural development, specifically the success of their OTOP Program in global market and discusses the potential of Indonesia to adopt similar program for market expansion and poverty alleviation.